2020
DOI: 10.1109/jstars.2020.2980381
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Flood Impact on Swiss Floodplains Using Interannual Time Series of Satellite Imagery

Abstract: Pressure on the biodiversity of ecosystems along many rivers is growing continuously due to the increasing number of hydropower facilities regulating downstream flow and sediment regimes. Despite a thorough understanding of the shortterm processes and interactions at this hydro-biosphere interface, long-term analyses of the impacts on floodplain dynamics are lacking. We used inter-annual Landsat 4, 5, 7 and 8 time series to analyze the effects of hydrological events on floodplain vegetation in four mountainous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Monitoring the establishment and recovery of vegetation in floodplains is essential for assessing the management needs of flow regimes and the success of restoration initiatives in river systems worldwide [35][36][37]. Empirical evidence about the differences in hydrologic and edaphic conditions along slopes, both geographically and temporally, is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the establishment and recovery of vegetation in floodplains is essential for assessing the management needs of flow regimes and the success of restoration initiatives in river systems worldwide [35][36][37]. Empirical evidence about the differences in hydrologic and edaphic conditions along slopes, both geographically and temporally, is insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature shows that Landsat time series have been used in studies on glacier dynamics, detecting glacial lakes, their expansion, and associated floods in different mountain regions such as HKH, Central Asia, and European Alps (Huang et al 2018;Ma et al 2021;Veh et al 2018;Yan et al 2018;Zheng et al 2019). In addition, changes in a forest in wetland areas of China were investigated, and flood impact on Swiss floodplains was also analyzed (Milani et al 2020;Wu et al 2020). However, we found that no studies are using Landsat time series to analyze abrupt changes in a dry mountain region, such as the eastern Hindu Kush.…”
Section: Introductionmentioning
confidence: 99%